The Indian ultrasound paradox - Mevlude Akbulut-Yuksel; Daniel Rosenblum (Institute for the Study of Labor (IZA), 2012)
The liberalization of the Indian economy in the 1990s made prenatal ultrasound technology affordable and available to a large fraction of the population. As a result, ultrasound use amongst pregnant women rose dramatically in many parts of India. This paper provides evidence on the consequences of the expansion of prenatal ultrasound use on sex-selection. We exploit state-by-cohort variation in ultrasound use in India as a unique quasi-experiment. We find that sex-selective abortion of female fetuses is rising in states with a slow expansion of ultrasound relative to those states with a rapid expansion of ultrasound. Thus, our findings suggest that the recent rapid spread of ultrasound is not causing higher rates of sex-selection in India.
urn:nbn:de:101:1-201203064030
Keywords: J13; J16; O1; 330; ultrasound; sex-selective abortion; India; Medizintechnisches Gerät; Schwangerschaftsabbruch; Geschlecht; Feldforschung; Indien